Pengaruh Pertumbuhan Ekonomi, Inflasi, BI Rate dan Nilai Tukar Rupiah terhadap Nilai Aktiva Bersih (NAB) Reksadana Syariah di Indonesia - Refi Mariska Junaidi; Fira Nurafini (Jurnal Ilmiah Ekonomi Islam, 2026)
The net asset value (NAV) of Islamic mutual funds in Indonesia has fluctuated significantly in recent years and remains lagging behind conventional mutual funds. This situation creates uncertainty for investors and indicates the influence of external factors, particularly macroeconomic variables, on the performance of Islamic mutual funds. The main focus of this research is to identify the influence of macroeconomic indicators, including economic growth, inflation, the BI Rate, and the rupiah exchange rate, on the NAV of Islamic mutual funds in Indonesia. The data used is secondary data with a monthly time series pattern. This secondary data was obtained from official publications released by Bank Indonesia, the Financial Services Authority, the Ministry of Trade of the Republic of Indonesia, and the World Bank. The data period studied covers the period from April 2016 to September 2025. Data analysis uses a Vector Error Correction Model (VECM) approach. The long-term VECM estimation results indicate that economic growth, the BI Rate, and the rupiah exchange rate significantly influence the NAV of Islamic mutual funds. Meanwhile, the inflation variable does not show a significant effect on the NAV of Islamic mutual funds in the long term.